Gonadectomy in conditions affecting sex development: a registry-based cohort study. Issue 6 (4th May 2021) - Lucas-Herald, Angela K; Bryce, Jillian; Kyriakou, Andreas; Ljubicic, Marie Lindhardt; Arlt, Wiebke; Audi, Laura; Balsamo, Antonio; Baronio, Federico; Bertelloni, Silvano; Bettendorf, Markus; Brooke, Antonia; Claahsen van der Grinten, Hedi L; et al.
Abstract : Objectives: To determine trends in clinical practice for individuals with DSD requiring gonadectomy. Design: Retrospective cohort study. Methods: Information regarding age at gonadectomy according to diagnosis; reported sex; time of presentation to specialist centre; and location of centre from cases reported to the International DSD Registry and who were over 16 years old in January 2019. Results: Data regarding gonadectomy were available in 668 (88%) individuals from 44 centres. Of these, 248 (37%) (median age (range) 24 (17, 75) years) were male and 420 (63%) (median age (range) 26 (16, 86) years) were female. Gonadectomy was reported from 36 centres in 351/668 cases (53%). Females were more likely to undergo gonadectomy ( n  = 311, P  < 0.0001). The indication for gonadectomy was reported in 268 (76%). The most common indication was mitigation of tumour risk in 172 (64%). Variations in the practice of gonadectomy were observed; of the 351 cases from 36 centres, 17 (5%) at 9 centres had undergone gonadectomy before their first presentation to the specialist centre. Median age at gonadectomy of cases from high-income countries and low-/middle-income countries (LMIC) was 13.0 years (0.1, 68) years and 16.5 years (1, 28), respectively ( P  < 0.0001) with the likelihood of long-term retention of gonads being higher in LMIC countries. Conclusions: The likelihood of gonadectomy depends on the underlying diagnosis, sex of rearing and the geographical setting. Clinical benchmarks, which can be studied across all forms of DSD will allow a better understanding of the variation in the practice of gonadectomy.